The grand domestic revolution : a history of feminist designs for American homes, neighborhoods, and cities - Hayden, Dolores (MIT Press, 1981)
"This is a book that is full of things I have never seen before, and full of new things to say about things I thought I knew well. It is a book about houses and about culture and about how each affects the other, and it must stand as one of the major works on the history of modern housing." - Paul Goldberger, The New York Times Book Review